Design of Photovoltaic Systems in Industrial Electrical Systems Considering Power Quality - Alvarino, Natalia Ivaneth Luna; Santos, Vladimir Sousa; González, Jairo Ricardo (International Journal of Energy Economics and Policy, 2024)
This paper presents a comprehensive design methodology for photovoltaic systems (PVS) integrated into industrial electrical systems (IES), with a specific focus on preserving power quality (PQ). The 10-step methodology, ranging from initial interviews to detailed technical, energy, and economic assessments, is novel for its multi-factorial approach that combines an Excel application with ETAP software, prioritizing considerations for PQ. Evaluation across four scenarios demonstrated varying outcomes. In the worst-case technical and energy scenario, PVS installation on Point of Common Connection without PQ mitigation led to significant increases in harmonics and no reduction in energy consumption. Conversely, the best technical and energy scenario involved distributing PVS across load buses with PQ mitigation, resulting in a 5% reduction in energy consumption and 27% lower energy losses. The economic evaluation indicated a three-year payback period in all scenarios, primarily attributed to increased costs for PQ problem mitigation equipment. It was also observed that reducing losses and energy consumption limits the economic benefits of installing PVS in IES. This methodology serves as a valuable guide for designing PVS in IES, incorporating technical, energy, economic, and PQ considerations.